Territorial development Quinoa: a catalyst for innovation - Bazile, Didier (Perspective, 2013)
<span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value="{"1":2,"2":"The International Year of Quinoa (IYQ) in 2013 celebrates this Andean plant for its potential contribution to the fight against hunger and poverty. The development of this sector can also have a territorial impact, depending on the context and on the accompanying process, as shown by the comparison between the Salars region in the south of the Bolivian Altiplano, the Central Chile region and the Mapuche region in southern Chile."}" data-sheets-userformat="{"2":577,"3":[null,0],"9":0,"12":0}">Versión en español del artículo <span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value="{"1":2,"2":"The International Year of Quinoa (IYQ) in 2013 celebrates this Andean plant for its potential contribution to the fight against hunger and poverty. The development of this sector can also have a territorial impact, depending on the context and on the accompanying process, as shown by the comparison between the Salars region in the south of the Bolivian Altiplano, the Central Chile region and the Mapuche region in southern Chile."}" data-sheets-userformat="{"2":577,"3":[null,0],"9":0,"12":0}">Version française de l'article <span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value="{"1":2,"2":"The International Year of Quinoa (IYQ) in 2013 celebrates this Andean plant for its potential contribution to the fight against hunger and poverty. The development of this sector can also have a territorial impact, depending on the context and on the accompanying process, as shown by the comparison between the Salars region in the south of the Bolivian Altiplano, the Central Chile region and the Mapuche region in southern Chile."}" data-sheets-userformat="{"2":577,"3":[null,0],"9":0,"12":0}">The International Year of Quinoa (IYQ) in 2013 celebrates this Andean plant for its potential contribution to the fight against hunger and poverty. The development of this sector can also have a territorial impact, depending on the context and on the accompanying process, as shown by the comparison between the Salars region in the south of the Bolivian Altiplano, the Central Chile region and the Mapuche region in southern Chile.